When feature-based production capabilities challenge operations: Drivers, moderators, and performance. Issue 2 (30th December 2019) - De Giovanni, Pietro
Abstract : Purpose: The purpose of this paper is to explore the influence that competitors and supply chain (SC) partners have on firms' feature-based production capabilities (FBPC). Also, it analyzes the consumers' customization options, the operational challenges and the need for servitization as a service-operations strategy to bypass the product complexity created through features. The author assesses the impact of FBPC on performance and uses some moderators to explore the operational implications in depth. Design/methodology/approach: The author tests research hypotheses through structural equation modeling using a sample of 172 manufacturing firms. The author analyzes the links existing among constructs and tests the influence of certain operational moderators within the network of relationships. Findings: FBPC are highly dictated by competitors' and SC partners' decisions, while servitization is a vital prerequisite to guarantee a valuable customization option. Although operational performance is highly challenged by FBPC, only good consumer experiences with features enhance economic performance. The analysis of moderators reveals that advanced planning systems, vendor managed inventory and distribution requirement planning enable firms to better exploit their operations. Total quality management helps firms to offer higher levels of servitization while reverse logistics needs careful evaluation to balance the trade-offs between higher operational performance and supply structure changes. Originality/value: This research empirically tests the influence of both competitors and suppliers when firms acquire FBPC. The author investigates consumers' requests for features and the benefits that servitization can supply when goods become too complex. The author tests how FBPC affect operations as well as the implications for economic performance. Finally, the author searches for moderators to assess the overall economic benefits of FBPC and better appreciate the operational implications.